Novel continuous self-baking anode aluminum electrolysis device and method

By forming 4 open sorting grooves and optimized related structures in the new type of self -roasted anode aluminum electrolyte, the intermittent operation and frequent pole replacement of large -scale pre -baked anode electrolytes are solved, and lower electrolyte voltage drops and more more High current efficiency reduces production costs.

CN119372716APending Publication Date: 2025-01-28唐国蓉
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411614194.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing large prebaked anode electrolytic tanks have intermittent operation and frequent electrode replacement, resulting in unstable internal production environment, and it is difficult to further reduce electrolytic energy consumption and production costs.

Method used

Adopt a new type of continuous self -roasted anode aluminum electrolytic device, and the design of 4 open sorting grooves in the lower half of the anode, optimizing the insulation heating cover and gas collecting box to improve the anode frame, support beam and asphalt smoke purification device Material and structure.

Benefits of technology

The significant thinning of the air bubble layer under the anode bottom, reducing the production pole distance and electrolyte voltage decrease, improved the current efficiency, reduced production costs, and provided the foundation for further reducing the voltage of the slot.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372716A_ABST
    Figure CN119372716A_ABST
Patent Text Reader

Abstract

The invention discloses a novel continuous self-baking anode aluminum electrolysis device and method. The novel continuous self-baking anode aluminum electrolysis device comprises an aluminum electrolysis cell body, an anode structure, an anode frame, a supporting beam, an asphalt smoke purification device, a heat insulation cover plate and a gas collection feeding box. According to the invention, some problems and defects of a novel efficient environment-friendly aluminum electrolysis cell are solved, an anode structure comprising an anode carbon body, a conductive unit group and an anode branch bus is improved and optimized, four slotted grooves are ensured to be formed in the lower part of a continuous self-baking anode, a bubble layer under the bottom of the anode is thinned during production, and the electrolyte voltage drop can be greatly reduced; the material and the structure of the heat insulation cover plate are improved and optimized, and when the heat income of the electrolytic cell is greatly changed, a method for adjusting the thickness of the heat insulation cover plate can be used for keeping good heat balance and normal cell conditions, so that the work of greatly reducing the cell voltage is realized, and the potential is great. Materials and structures of the anode frame, the supporting beam, the asphalt fume purifying device and the gas collecting and feeding box are reasonable and practical, the service life is longer, and manufacturing, operation and replacement are convenient, so that the novel continuous anode electrolytic cell technology can be better applied to actual production. By applying the new technology, the energy consumption, carbon consumption and carbon emission of aluminum electrolysis production can be greatly reduced, the production cost of an enterprise can be reduced by about 1500 yuan / T.AL, and contributions are made to energy conservation and carbon reduction in the electrolytic aluminum industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum electrolysis, and in particular relates to a novel continuous anode aluminum electrolysis device and method. Background Art

[0002] As a kind of aluminum electrolysis technology based on continuous anode that has appeared in the development of aluminum electrolysis technology, self-baking cell aluminum electrolysis has made great contributions to the development of the electrolytic aluminum industry. Self-baking anode aluminum electrolysis cells have major defects: large anodes (width is more than 4 times that of existing cells) make anode gas discharge poor, the bubble layer under the anode bottom is thick, and alumina materials are added in the shell pressing process every 2-3 hours, resulting in large changes in alumina concentration, unevenness and a large amount of precipitation. Production requires high pole distance, high production cell voltage, high electrolysis energy consumption, and large material consumption; the asphalt fume in the electrolysis process is large and cannot be collected and processed in a centralized manner, resulting in a poor factory environment; there are many production operation procedures, low mechanization and automation, and high labor intensity. These inherent defects cannot be completely solved, resulting in the gradual replacement of self-baking anodes by large pre-baked anode electrolysis cells. Modern large pre-baked cells are the product of scientific and technological progress. The structure of the electrolysis cell has been greatly optimized and improved, the anode has become narrower, and the alumina feeding is controlled by the cell control system according to the program, and the feeding is added about once every 2 minutes, which greatly improves the performance. From the 1960s to around 2013, the DC power consumption of some of the most advanced electrolytic cells dropped to around 12400Kwh / TA, which is about 4000Kwh / T.AL lower than that of the large anode self-baking cell. However, in the past decade, the work of continuing to significantly reduce the cell voltage and power consumption in production has slowed down. After the cell voltage dropped to around 3.8V, it basically did not drop. The biggest disadvantage and shortcoming of the existing pre-baked cell is that the production is intermittent operation. Dozens of anodes in the cell are staggered and distributed in various parts of the electrolytic cell. The anodes must be replaced continuously to ensure continuous production. Frequent pole replacement work causes great interference to the internal production environment of the electrolytic cell, affecting the material balance, thermal balance and electromagnetic balance. Although the width of the current pre-baked anode is smaller than that of the original self-baking cell anode, it is still relatively wide. Only by reducing the width to less than 400mm can the thickness of the bubble layer be minimized. In recent years, new energy-saving technologies and materials have been developed, such as fully graphitized cathodes, wettable cathodes, copper-embedded steel rods, slotted anodes, and perforated anodes. These materials and technologies reduce cathode voltage drop, electrolyte voltage drop, anode voltage drop, etc. The existing technologies and related energy-saving materials have been fully implemented, which can reduce the cell voltage to below 3.7V and the DC power consumption to below 1200Kwh / T.AL. However, in fact, after the DC power consumption dropped to around 12400Kwh / T.AL, it has basically not decreased for many years. The electrolytic production has encountered a technical bottleneck. It has become very difficult to solve these problems within the structural framework of large prebaked anode electrolytic cells.

[0004] Patents CN 215517666U and CN 115012002 A disclose a new type of environmentally friendly aluminum electrolytic cell, which is a "new type of continuous anode electrolytic cell". It inherits the advantages of modern large-scale prebaked cells, keeps the overall structure of the existing cells unchanged, and improves and optimizes some structures in the existing cell structure that are not conducive to production, technological progress and cost reduction. The dozens of prebaked anodes (groups) with uneven heights and constantly replaced in the corresponding positions are replaced with continuous self-baked small anodes with better exhaust, and the asphalt smoke is effectively purified. Materials such as alumina only enter the electrolyte solution from a closed channel, and alumina and electrolyte powder mixture are replaced with heat-insulating covers to cover anodes. In this way, the electrolytic production process is shortened and optimized, labor productivity is greatly improved, production technical indicators are greatly improved, and production costs are greatly reduced. Although this patented technology has better solved some key problems of modern large-scale prebaked cells that are not conducive to production, technological progress and cost reduction, it still has some defects and shortcomings, and it is difficult to implement and its role and effect cannot be fully exerted. There are defects in the anode structure. The size of its continuous self-baking anode is equivalent to that of the existing pre-baked anode. One anode corresponds to two anode branch busbars and four conductive unit groups. The four conductive unit groups are located on the same straight line. Four grooves are formed on the lower part of the anode in a straight line, of which only two slotted grooves can be formed on the edges. Since the two middle grooves have no slots, the anode gas cannot be discharged in time. The bubble layer under the anode bottom palm is still similar to the flat bottom pole, so the production pole distance cannot be reduced, otherwise it will trigger the secondary reaction of aluminum. The isolation cloth is installed on the inner wall of the anode box, which is difficult to operate. The anode box is welded, which is troublesome to install and remove and easy to damage. The production of the electrolytic cell support beam is more troublesome, and the corrosion resistance to high-temperature HF is not strong, which affects the service life. The material and structure of the electrolytic cell asphalt fume purification device are not very applicable. The main body is processed from galvanized steel pipes into an integral pipeline with many bends, which occupies a large space, affecting the operation of salvaging carbon slag in production, and is difficult to make and replace. The material and structure of the thermal insulation cover are defective. The main material is calcium silicate board, which is a hard material. It is difficult to cut and produces harmful dust. The thermal conductivity is unstable. It is difficult to adjust after the heat input changes and difficult to control. Ordinary steel is not anti-magnetic, which affects the operation. The material and structure of the gas collection feed box are not good enough, and the corrosion resistance to high-temperature HF is not strong, which affects the operation and service life. These defects and problems make it difficult to implement new technologies. Some production operations are difficult and troublesome, some parts are easily damaged and difficult to replace and maintain, and the actual effect is difficult to achieve expectations. There are still great difficulties in actual production and large-scale applications. Summary of the invention

[0005] The defects and shortcomings of the above-mentioned prior art are well solved by a new type of continuous self-baking anode aluminum electrolysis device and method provided by the present invention. The present invention ensures that there are 4 slit grooves in the lower half of the continuous self-baking anode, and the bubble layer under the bottom palm of the anode is thinner during production. The thickness of the aerogel material in the thermal insulation cover plate can be adjusted according to the heat income during production, so as to maintain a good thermal balance and normal cell conditions, so that the work of significantly reducing the cell voltage can be implemented and has great potential. The material structure of the anode frame, support beam, asphalt fume purification device, gas collection feed box, etc. is better, easy to make, operate and replace, and has a longer service life. The improved structure and method allow the new continuous anode electrolytic cell technology to be better applied to actual production, with good effect and great potential, and can make great contributions to the electrolytic aluminum industry, energy conservation and carbon reduction, and enterprises to reduce production costs.

[0006] The present invention is achieved through the following technical solutions.

[0007] A novel continuous self-baking anode aluminum electrolysis device comprises: an aluminum electrolysis cell body, an anode structure, an anode frame, a support beam, an asphalt fume purification device, a heat insulation cover plate, and a gas collecting feed box. The support beam is installed and fixed on the slot edge plate of the electrolytic cell shell, and its main function is to place and fix the anode frame, asphalt purification device, thermal insulation cover plate, gas collecting feed box, etc. The anode frame is placed and fixed on the support beam, and its main function is to shape the anode and hold the paste. The anode structure is connected to the anode busbar, including an anode carbon body, a conductive unit group and an anode branch busbar. Most of the anode carbon body and the conductive unit group are located in the anode frame, and a part of them extends from the lower mouth of the anode frame into the electrolyte to participate in the electrolytic production. The asphalt fume purification device is used to treat the asphalt fume generated in the aluminum electrolytic production. The function of the thermal insulation cover plate is to completely seal the upper part of the electrolytic cell, greatly reduce the heat dissipation loss in the upper part of the cell and the leakage of smoke and dust, and eliminate or reduce the precipitation at the bottom of the furnace. The gas collecting feed device allows aluminum oxide to enter and evenly add to the electrolyte liquid in the cell, and collects the smoke generated during the electrolytic production here for a preliminary purification treatment, and then to the purification system for treatment.

[0008] The anode carbon body of the present invention is a continuous self-baking anode, which consists of three parts: a solid anode, a liquid paste layer, and an anode particle layer. The total height is about 1200 mm, the solid anode height is about 900 mm, the anode width is about 1000 mm, and the length is about 1500 mm. The number of anodes is less than that of the prebaked anodes of the same prebaked tank, and the specific number is determined according to the anode tank size and current density. The raw material of the anode carbon body is anode particles, which are composed of aggregates and binders, with the aggregate accounting for about 80% and the binder accounting for about 20%. The aggregate is high-quality forged coke and residual pole fragments, and the binder is high-quality asphalt. The mother pole of the continuous self-baking anode is made by casting and baking outside the tank, and there are 4 slotted grooves at the bottom of the anode carbon body. Before production, when the cell is roasted and put into production, the mother electrode is installed to the corresponding position of the electrolytic cell, and the stainless steel plate is assembled into an anode frame to surround the mother electrode. One anode corresponds to four conductive units and is implanted in the anode carbon body. The top conductive unit is hooked on the anode branch busbars on both sides of the anode busbar during production. The corresponding four anode branch busbars are symmetrically welded or crimped on both sides of the anode aluminum busbar, and the distance between the two branch busbars on the same side is about 320mm. During production, the bottom anode participates in the electrochemical reaction and is continuously consumed. At the same time, under the action of the Joule heat generated by the heat energy and current in the cell passing through the inside of the anode, the anode particles and the new solid anodes baked out are also continuously melted synchronously. As long as a certain amount of anode particles are regularly added to the upper layer of the anode, the structure and morphology of dozens of anodes in the cell remain unchanged until the cell is stopped for overhaul and the cell is adjusted out and restarted next time. The edge of the upper conductive unit is about 6mm away from the inner wall of the anode frame. During production, the anode raw materials will shrink after being baked into a solid anode at the bottom of the anode frame. The conductive unit material will expand thermally and extend out of the edge of the solid anode in the length direction of the anode. Then, when the temperature is higher than 660℃, the aluminum melts into aluminum liquid and enters the tank. Four slit grooves are formed at the bottom of the anode. The spacing between the two parallel slit grooves is about 320mm. The distance from the middle part of the anode bottom palm to the slit groove or the edge of the anode is less than 200mm. The distance of the anode bubble escape becomes shorter, and the gas at the anode bottom palm is discharged in time and fully. Compared with the anode of the original new high-efficiency and environmentally friendly aluminum electrolytic cell, its structure is more reasonable and suitable for the production of cell voltage reduction. The anode of the new high-efficiency and environmentally friendly aluminum electrolytic cell can only form two slit grooves at the edge. Since the two middle grooves do not form slits, the anode gas cannot be discharged in time. The bubble layer under the anode bottom palm is still similar to the flat bottom pole without slits, so the production pole distance cannot be reduced, otherwise it will trigger the secondary reaction of aluminum. The bubble layer under the anode bottom of the present invention is thinner, about 6 mm thinner than the bubble layer under the anode bottom of the existing cell, and the current efficiency will not be reduced when maintaining a lower inter-electrode distance, and the electrolyte voltage drop during production can be reduced by about 180 mV.

[0009] The conductive unit group of the present invention is composed of a plurality of conductive units connected by buckles. The conductive unit is composed of two "7"-shaped aluminum blocks, a plurality of aluminum soft strips and a thin steel strip. The thin steel strip is at the edge. The aluminum soft strip is about 400 mm long and about 630 mm wide. The specific length and width of the aluminum soft strip are determined according to the anode size and the travel distance of the anode aluminum busbar. The number of aluminum soft strips and the size of the thin steel strip are mainly determined according to the safety strength and current density of the material. Several materials can be connected into a solid whole by diffusion welding and other methods. One anode corresponds to four conductive unit groups implanted in the anode carbon body. The top conductive unit is buckled on the anode branch busbars located on both sides of the anode busbar during production. The edge is about 6 mm away from the upper inner wall of the anode box. The spacing between the two groups on the same side is about 320 mm, and the spacing between the conductive unit groups on both sides is about 220 mm. The anode branch busbar is made of thick aluminum plate or copper plate. The four anode branch busbars corresponding to one anode are symmetrically welded or crimped on both sides of the anode aluminum busbar. The spacing between the two branch busbars on the same side is about 320 mm. In this way, during production, direct current is introduced from the anode busbar into the anode carbon body, and when the anode busbar moves up and down, it drives the anode to move up and down. The conductive unit is firmly bonded and sintered together inside the anode, and the conductive unit material undergoes thermal expansion, extending out of the edge of the solid anode in the length direction of the anode. Below the high temperature of 660℃ at the anode, part of the aluminum melts into aluminum liquid and enters the tank, and four slit grooves are formed at the bottom of the anode. Compared with the anode branch busbar and conductive unit of the original technology, the structure is more scientific and reasonable. During production, it is ensured that there are four stable slit grooves at the bottom of the anode, and the spacing between the parallel slit grooves is about 320mm. The distance from the middle part of the anode bottom palm to the slit groove or the edge of the anode is less than 200mm. The four grooves formed by the original structure are in a straight line, of which only two slit grooves are formed at the edge. Since the two middle grooves do not form slits, the bubble layer under the anode bottom palm is still effectively thinned, and the production pole distance cannot be effectively reduced. The newly added thin steel sheet will not melt until it is close to the electrolyte, which increases the strength of the conductive unit group, ensures that the conductive unit is not too thick but has sufficient strength and does not affect the original aluminum grade, and is easy to operate. The anode branch busbar and conductive unit structure of the present invention are more reasonable and suitable for the production of reduced slot voltage. During production, the bubble layer under the anode bottom palm is thinner, about 6mm thinner than the existing slot, which can reduce the electrolyte pressure by about 180mV.

[0010] The support beam of the present invention is installed and fixed on the edge plate of the electrolytic cell shell, and the number is N / 2+1, where N is the number of anodes in a cell. Its main function is to place and fix the anode box, asphalt purification device, heat insulation cover plate, gas collection feed box, etc. The material of the support beam is a thick stainless steel plate, and the sealing part in the slot is coated with a ceramic-based aerogel coating. There are two "L"-shaped grooves on the top of the beam, the groove depth is 5mm, the length of the groove is 2mm longer than the anode box, and the width of the groove is 1mm greater than the thickness of the anode box steel plate. The electrolytic cell support beam of the original technology uses high-temperature resistant reinforced concrete or thick steel plate as the main body, and the high-temperature calcium silicate board and ceramic fireproof cloth are cast and bonded to the bottom and side of the beam together. The production is relatively complicated. The high-temperature calcium silicate board and ceramic fireproof cloth will be damaged and fall into the tank under long-term high temperature. Ordinary steel or high-temperature resistant reinforced concrete is subject to high-temperature corrosion, and the service life is shortened, thereby affecting the practical application of the technology. The support beam of the present invention is simple to manufacture, the material performance is excellent and stable, it is more resistant to high-temperature corrosion, and the service life is longer.

[0011] The anode frame of the present invention is a rectangular frame structure assembled from a plurality of pre-made stainless steel plates. It is used to enclose the mother pole of the continuous self-baking anode after it is hoisted into the slot. Its main function is to shape the anode and hold the paste. The inner cavity of the frame is the same size as the upper part of the carbon anode, with a height of about 1400mm. The lower opening is placed in the "L"-shaped groove of the two support beams. The upper opening and the reinforced flat web on the door frame are crimped with fasteners. Four seams are opened on the flat web for the conductive unit group to pass through, connected to the anode, and sealed with a soft object. The frame below the sealing part of the sealing plate of the heat insulation cover plate and the gas collection feed box is coated with a ceramic-based aerogel coating to prevent and reduce corrosion such as hydrogen fluoride. An anode particle entry device is arranged on the upper outer wall of the frame, and the anode paste is added to the anode frame from then on. An anode particle distribution plate is built in to allow the anode particles to fall on the anode body in a relatively dispersed and even manner. A threaded pipe joint is arranged downward to connect with the asphalt fume purification device. In addition, a pneumatic clamping device is also arranged on the flat belly plate at the top of the anode frame, which is composed of a cylinder and a clamping plate and is used when lifting the busbar. The isolation cloth is cancelled on the inner wall, and the edge of the upper conductive unit is arranged about 7mm away from the upper inner wall of the anode frame. During production, the conductive unit material undergoes thermal expansion. When it reaches the lower part of the anode frame, the solid anode edge is squeezed out in the length direction of the anode, but there is still a gap of about 2mm from the inner wall of the anode frame to ensure that the anode can move up and down. The original technology is to install a continuous isolation cloth on the inner wall of the anode box during production, which is difficult to operate and has poor practicality. The anode box is welded, which is troublesome to install and remove and is easy to damage. The material is ordinary steel, which has low strength and poor corrosion resistance. The anode frame of the present invention has a more reasonable structure and material, which satisfies the functions of anode shaping and holding paste, ensures that the anode can move up and down, etc. It is simple and convenient to operate, easy to install and remove, and has high material strength, corrosion resistance, and long service life.

[0012] The asphalt smoke purification device of the present invention is composed of a main pipeline, an upper smoke pipe, a lower smoke pipe and some joints. The two main pipelines are composed of straight stainless steel pipes and some bent pipes and flexible joints, which are symmetrically placed on the support beam. They are simpler than the original asphalt smoke purification device body, occupy less space, and are convenient for operations such as salvaging carbon slag. There are threaded joints on the pipelines to connect the upper smoke pipe and the lower smoke pipe. The upper smoke pipe is an assembly connected by an ordinary steel pipe and a hose, which is connected to the smoke exhaust holes on each anode frame. The lower smoke pipe is a silicon nitride combined with silicon carbide tube that is resistant to high-temperature corrosion. It is located between the two rows of anodes A and B and extends downward to the surface of the high-temperature electrolyte by about 5 cm. Compared with the electrolytic cell asphalt smoke purification device of the original technology, the overall structure is more compact, easier to manufacture and install, the stainless steel pipe has a longer service life, and is easier to operate and replace, which is conducive to the salvaging of carbon in production and has stronger practicality. Due to the negative pressure, the asphalt smoke generated on the upper part of the anode enters the upper smoke pipe of the asphalt smoke purification device from the smoke exhaust holes on the upper part of each anode box, and then goes to the main pipe of the asphalt purification device, and then goes to the lower smoke pipe and is discharged at about 5 cm above the surface of the high-temperature electrolyte liquid at about 950°C. In the small high-temperature space at about 900°C, harmful high-molecular compounds such as benzopyrene are cracked and pyrolyzed to become harmless small-molecular compounds. When they encounter the oxygen introduced from the air inlet pipe of the middle insulation cover plate, they are burned and become harmless gases. They enter the gas collecting feed box for initial purification, and then go to the purification system for treatment, making the production site environmentally friendly and clean.

[0013] The heat-insulating cover plate of the present invention includes a middle heat-insulating cover plate and an edge heat-insulating cover plate, and the materials are stainless steel plate, aerogel material, high-temperature ceramic fireproof cloth, silicon nitride combined with silicon carbide tube, etc. Among them, the edge heat-insulating cover plate is in a "7" shape, and some joints for connecting asphalt smoke pipes are provided, and the middle heat-insulating cover plate is provided with an air intake pipe-silicon nitride combined with silicon carbide tube. The edge heat-insulating cover plates are placed on the surrounding groove edge plates, close to the anode frame and the surrounding groove shell outer walls and close to each other, and the middle heat-insulating cover plates are close to each other or to the gas collection feed box and close to the two rows of anode frames A and B. In this way, the upper part of the electrolytic cell is completely sealed, and the electrolyte liquid and anode, hot gas, dust, main pipeline of the asphalt purification device and the lower smoke pipe are completely sealed in the cell. No alumina and electrolyte blocks fall into the cell, eliminating or reducing the bottom sedimentation of the furnace, the bottom of the cell is clean, the horizontal current is greatly reduced, the electrolyte liquid is clean and smooth, the concentration of alumina is uniform, the anode is better wetted, and the phenomenon of idle current such as anode effect, side leakage, and anode long bag can be basically eliminated or greatly reduced. The current flows vertically from the anode to the cathode through the electrolyte liquid, the gas is discharged in time, the aluminum electrolysis is smooth, and the current efficiency will be greatly improved. At the same time, there is less leakage of flue gas and dust, and the production site environment is also better. The function of the air intake pipe of the central insulation cover is to introduce external oxygen to burn cracking, cracking and cracking of asphalt smoke and CO. The calcium silicate board in the structure of the thermal insulation cover of the original technology is a hard material, which is difficult to cut, the dust produced is harmful, the thermal conductivity has a large range of variation and is unstable, it is not easy to produce a thermal insulation cover suitable for production needs, it is difficult to adjust after the heat input changes, it is not easy to regulate, and the matching thermal insulation cover is difficult to determine in a short time, which has a great impact on production and indicators. At the same time, operations such as aluminum and carbon slag are easily damaged during production, and the non-magnetic properties of ordinary steel affect the operation of operations such as carbon slag and aluminum. Therefore, the overall operability is poor in production and is not easy to regulate. These problems are not well solved and are difficult to be applied in production on a large scale. The aerogel material in the thermal insulation cover of the present invention is an environmentally friendly soft material, which is easy to be made into various shapes and thicknesses, and the thermal conductivity is only about 0.02W / m.K and is relatively stable, which is lower than 0.034-0.1W / m.K of calcium silicate board and much lower than 10W / m.K of alumina. In this way, it is possible to produce a heat-insulating cover plate that matches the thermal balance of electrolytic production. When the heat input changes, it is easy to adjust. Stainless steel has high strength and anti-magnetic properties, a longer life, easy production and operation, and strong overall operability. This heat-insulating plate can greatly reduce the heat loss in the upper part of the tank and is easy to control. When the heat input of the electrolytic cell changes significantly, such as when the cell voltage drops by more than 50mV, the thickness of the aerogel material in the heat-insulating cover plate can be adjusted quickly, which reduces the heat loss in the upper part of the cell and maintains the thermal balance and normal cell condition of the electrolytic cell. This solves the problem of maintaining the upper part of the cell insulation and thermal balance after the cell voltage is significantly reduced, and provides a guarantee for the continued significant reduction of the cell voltage in electrolytic production. The existing heat loss in the upper part of the prebaked cell reaches 55%, which is equivalent to a voltage of about 1160mV, and has great potential.

[0014] The gas collecting feed box of the present invention is placed on the support beam, located at the original shelling and unloading place, and is composed of a box body, a feed pipe, a primary dividing plate, a secondary dividing plate, a smoking pipe, and a sealing plate. The sealing plate is composed of a stainless steel plate, an aerogel material, and a ceramic fireproof cloth. The box body, the feed pipe, the primary dividing plate, the secondary dividing plate, and the smoking pipe are made of stainless steel. The inner wall of the box body, the primary dividing plate, and the secondary dividing plate are coated with a ceramic-based aerogel coating, which enhances the corrosion resistance of hydrogen fluoride. The feed pipe is connected to the alumina material box unloader and is connected by a threaded connection. The smoking pipe is connected to the box body and the electrolytic cell cigarette support pipe and is connected by a threaded connection or a bolt. Compared with the electrolytic cell gas collecting feed box of the original technology, the material and structure are more reasonable and practical, the corrosion resistance of HF is enhanced, the production and installation are simpler, and the service life is long. The main functions of the gas collecting and feeding box are to allow alumina to enter the box from a closed channel and evenly add it to the electrolyte in the tank, and to collect the flue gas generated during electrolytic production, perform a preliminary purification, and then go to the purification system for treatment. The gas collecting and feeding box is connected to the electrolytic cell smoke pipe. The high-temperature small space sealed between the gas collecting and feeding box and the two rows of anodes is negative pressure. The generated flue gas will be concentrated and enter the gas collecting and feeding box without leakage, which greatly improves the environment around the tank and the factory. During production, the alumina discharged from the fixed volume falls downward, and the flue gas generated by electrolytic production moves upward into the box. The two meet, and harmful gases such as HF in the flue gas are adsorbed by alumina. After being initially purified, they are treated by the purification system outside the factory, and the discharged flue gas is more environmentally friendly. After passing through the two-stage dividing plates of the gas collecting and feeding box, the alumina is evenly dispersed in a large area of ​​electrolyte liquid, can quickly dissolve and diffuse to the entire tank, will not or rarely sink to the bottom of the furnace to produce precipitation, and the concentration of alumina in the electrolyte of the entire tank is uniform and relatively stable.

[0015] Beneficial technical effects of the present invention: The "new type of continuous anode aluminum electrolysis device and method" provided by the present invention improves and optimizes the anode structure in the "original new type of high-efficiency ring aluminum electrolysis cell", the production pole distance can be reduced by about 6mm, the electrolyte pressure drop is reduced by about 180mV, the improved heat insulation board can greatly reduce the heat dissipation loss of the upper part of the cell and is easy to control, effectively solves the problem of maintaining the upper part of the cell insulation and thermal balance after the cell voltage is greatly reduced, and provides a guarantee for the continued reduction of the cell voltage in electrolytic production. The present invention solves the problems and deficiencies in the materials, manufacturing, installation and operation of the anode box, support beam, asphalt smoke purification device, and gas collection feed box, and the goal of upgrading and transforming modern large-scale prebaked cells into new continuous anode electrolysis cells for production and operation can be better achieved. By applying the new technology of "a new type of continuous anode aluminum electrolysis device and method", the technical and economic indicators of electrolytic production are compared with the existing large-scale prebaked cells, the current efficiency is improved by about 3%, and the production cell voltage is reduced by about 400mV. By applying relevant energy-saving technologies and materials, the cell voltage can be further reduced. The production technical and economic indicators of the upgraded new trough have been significantly improved, and energy consumption, carbon consumption and carbon emissions have been greatly reduced, which can reduce the production cost of the enterprise by about 1,500 yuan / TAL. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram of the structure of the novel connected self-baking anode electrolytic cell of the present invention, Figure 2 The side view of the continuous self-baking anode. Figure 3 This is a cross-sectional view of the lower part (bottom palm) of the continuous self-baking anode. Figure 4 This is a cross-sectional view of the upper part of the continuous self-baking anode solid. Figure 5 is a schematic diagram of the structure of the conductive unit. Figure 6 This is a schematic diagram of the structure of the edge insulation cover. Figure 7 This is a schematic diagram of the structure of the central thermal insulation cover. Figure 8 This is the side view of the gas collection feed box. Fig. 9 This is a top view of the main pipeline of the asphalt fume purification device. Figure 1 In the figure, 1-aluminum liquid 2-high temperature electrolyte liquid 10-extension leg 3-electrolytic cell support beam 41-anode box 42-anode particle distribution plate 43-anode particle entry device 47-pneumatic clamping device 51-solid anode 52-liquid anode paste 53-anode particles 54-anode slit groove 61-anode branch bus 62-conductive unit 71-asphalt smoke purification device main pipeline 72-asphalt smoke upper pipe 73-asphalt smoke lower pipe 81-edge thermal insulation cover 82-middle thermal insulation cover 9-gas collecting feed box. DETAILED DESCRIPTION

[0017] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0018] like Figure 1-9 As shown, it is a new type of continuous anode aluminum electrolysis device, which improves and optimizes the anode structure and thermal insulation cover of the original "new type of high-efficiency ring aluminum electrolysis cell", and solves the difficulties in the production, installation and operation of the anode box, support beam, asphalt smoke purification device, and gas collection feed box, as well as the problems in service life. The application of "a new type of continuous anode aluminum electrolysis device and method" to upgrade and transform modern large-scale prebaked cells into new types of continuous anode electrolysis cells, or to build new types of continuous anode electrolysis cells can be better implemented and realized, with better results, energy saving and carbon reduction, and lower production costs, and also lay a solid foundation for further substantial reductions in cell voltage.

[0019] Before production, N / 2+1 support beams (3) are installed and fixed on the plate along the electrolytic cell, and the anodes (51-53) cast and baked outside the cell are hoisted to the corresponding positions in the cell. The four conductive unit groups (62) are sintered together with the anodes. The anode frame (4) is made of stainless steel plates prepared in advance to enclose the anode. The inner wall space of the anode frame is the same size as the upper part of the anode, and the height is about 1400mm. The lower opening is placed in the two "L"-shaped grooves on the top of the two technical beams. The upper opening is crimped with the flat web on the portal frame (the flat web of the existing cell is widened) by fasteners. Four slits are opened on the flat web for the conductive unit group to pass through, which is sealed with soft objects, and the conductive unit is hung on the anode branch busbar (61).

[0020] Carry out various commissioning before production until acceptance.

[0021] Various raw and auxiliary materials are loaded into the tank as planned, the main pipeline (71) of the asphalt fume purification device is installed on the support beam (3) and the lower smoke pipe (73) is connected, the heat insulation cover plate (81, 82) and the gas collection feed box (9) are placed on the support beam (3), the feed pipe (92) of the gas collection feed box is connected to the alumina material box, and the smoke pipe (96) is connected to the electrolytic cell smoke pipe. The heat insulation cover plate (81, 82) is installed, and the upper asphalt smoke pipe (72) of the asphalt fume purification device is connected to the smoke exhaust hole on the anode frame. At this point, such a new type of continuous self-baking anode electrolytic cell is completely formed, and some insulation tests are carried out. After passing the test, the baking start can be carried out.

[0022] The power is turned on to start roasting, a high-temperature, high-molecular-weight furnace side and a regular and stable furnace chamber are established, and normal production management is started.

[0023] During the production process, the numerous anodes (5) participating in the electrolytic reaction are consumed in the reaction, and at the same time, under the high temperature of the electrolyte and the internal electric heating, a part of the anode particle layer (53) is simultaneously melted into liquid paste (52), and a part of the liquid paste is sintered into solid anode (51). The overall shape of the anode is stable during production. In electrolytic production, the anode consumption rate is about 2 mm per day. The paste is added once a day or two from the feeding device (46) on the side of the anode frame. The overall shape of the anode remains stable and can meet the needs of continuous production. Since the conductive unit material is consumed along with the anode during production, the conductive unit (62) needs to be connected and the busbar lifting work needs to be carried out after a cycle. Some pneumatic clamping devices (47) are set on the flat belly plate on the upper part of the anode frame. The pneumatic clamping devices are composed of a cylinder and a clamping plate and are fixed to the front and rear of the conductive unit. When lifting the busbar, the cylinders at the corresponding positions are controlled by the slot control box and the air control box to push the conductive units (62) on the anode frames to the clamps and clamp them. The top conductive strip is removed from the anode branch busbar (61), connected to a conductive unit, and then installed on the anode branch busbar. There are 4 groups in total. First, operate 1 group, then 2 to 4 groups in sequence, and then lift the anode busbar to the corresponding position, tighten the conductive unit, release the clamp, and the operation is completed. The edge of the upper conductive unit is about 7mm away from the upper inner wall of the frame. When the temperature rises, linear expansion will occur. After the anode paste is heated and sintered to form a conductive solid anode, the volume will shrink. The lower conductive unit material (62) squeezes the edge of the anode in the length direction of the anode due to the increase in temperature, and is about 2mm away from the inner wall of the frame, ensuring that the anode structure can move up and down smoothly with the anode busbar. Further down, the aluminum below the 660℃ high temperature of the anode cone melts into aluminum liquid and enters the tank, automatically forming four slotted grooves (54) with the same depth at the inner lower part of the anode. The distance between the middle position of the anode and the slot or the edge of the anode is less than 200mm, and the escape distance of all bubbles at the bottom of the anode is shortened. The bubbles generated are discharged in time, and the bubble layer under the bottom of the anode will be reduced by about 6mm. The electrolyte pressure drop during production can be reduced by about 180mV compared with the existing large-scale prebaked anode tank; all anode bottoms are at the same level, and the production pole distance can be maintained at about 2mm lower than the prebaked tank under the same situation without reducing the current efficiency, which can reduce the electrolyte pressure drop by about 60mV; the metal conductive unit of a single anode conductor is implanted in the carbon anode and sintered into one with the carbon, and is hung on the anode branch busbar, so the voltage drop is about 70mV lower than that of the prebaked anode conductor; in this way, the tank voltage during production can be about 300mV lower than that of the modern large-scale prebaked tank. Since there is no pole change, production is more stable, no residual pole is generated, and the gross consumption of anode is also greatly reduced.

[0024] The gas collecting feed box is composed of a box body (91), a feed pipe (92), a primary material dividing plate (93), a secondary material dividing plate (94), a smoke pipe (95), and a sealing plate, wherein the sealing plate is composed of a stainless steel plate (96) and a ceramic fireproof cloth (97). During the production process, since the smoke pipe (95) of the gas collecting feed box is connected to the purification system, there is a negative pressure between the gas collecting feed box and the two rows of anodes, and the asphalt smoke generated on the upper part of the anode enters the upper smoke pipe (72) of the asphalt smoke purification device from the smoke exhaust holes on each anode frame, enters the main pipeline (71) of the asphalt purification device, and then enters the lower smoke pipe (73) and then enters the surface of the electrolyte liquid with a high temperature of about 950°C. The temperature rises to about 900°C, and harmful high molecular compounds such as benzopyrene are cracked and pyrolyzed to become small molecular compounds, which are burned by the oxygen introduced from the middle heat insulation cover plate air intake pipe (824) and become harmless gas, thus meeting the environmental protection requirements. During production, the material from the alumina material box enters the gas collecting and feeding box body (91) through the feeding pipe (92), passes through the two-stage material discharging distribution plates (93, 94), and falls relatively evenly. On the way, it meets the flue gas, absorbs harmful components such as HF in the flue gas, and falls into the electrolyte liquid surface. Since the electrolyte is clean and smooth, the alumina quickly dissolves and diffuses throughout the tank, and no precipitation is generated at the bottom of the furnace. The concentration of alumina in the electrolyte of the entire tank is uniform and stable, which can better wet the anode. In the late stage of the electrolytic cell startup, after the high-temperature and high-molecular ratio furnace side and legs are naturally formed, the tank chamber of the electrolytic cell is regular and stable, and the production is stable and efficient. During production, the flue gas flows upward and mixes with the alumina moving downward. The harmful components such as HF in it are absorbed, and become flue gas containing less harmful components such as HF, and enters the branch flue of the electrolytic cell from the box flue pipe (95), and then is discharged to the atmosphere after being treated by the purification system outside the factory.

[0025] The thermal insulation cover plates (81, 82) completely seal the upper part of the electrolytic cell, and are composed of stainless steel plates, aerogel materials, high-temperature ceramic fireproof cloth, and silicon nitride combined with silicon carbide tubes. The edge thermal insulation cover plate (81) is composed of 811, 812, and 813, and the middle thermal insulation cover plate (82) is composed of 821, 822, 823, and 824. Alumina only enters the electrolyte liquid from the constant volume feeder of the material box through the channel of the gas collecting feed box, ensuring the electrolytic production dosage. No excess material falls into the tank from the top, the furnace bottom is clean, the horizontal current in the aluminum liquid can be basically eliminated or greatly reduced, and the aluminum liquid fluctuation is reduced, which can reduce the production pole distance by about 4mm and reduce the electrolyte voltage drop by about 120mV; the tank chamber is regular and stable, the electromagnetic field is more balanced, the aluminum oxide concentration is uniform and relatively stable, and can better wet the anode. The anode effect, side leakage, anode long bag and other idle current phenomena can be basically eliminated or greatly reduced. The current flows vertically from the anode to the cathode through the electrolyte liquid, the gas is discharged in time, the aluminum electrolysis proceeds smoothly, and the current efficiency will be greatly improved; due to full sealing, there is less smoke and dust leakage, and the production site environment is also better. In order to lower the cell voltage and maintain normal production, two conditions must be met at the same time: first, the voltage drop at various parts of the electrolytic cell's electrical circuit is reduced, and second, the heat dissipation from the cell to the outside must also be reduced accordingly. The reduction must be equivalent to the reduction in heat input caused by the voltage reduction, so that normal production thermal balance and cell conditions can be maintained. The heat insulation cover plate provided by the present invention has a very low thermal conductivity of the aerogel material (822), which is about 0.02W / m·K and relatively stable. Thus, when the slot voltage is reduced, if the reduction exceeds 50mV, the thickness of the aerogel material is thickened to reduce the heat loss in the upper part of the slot, and the reduced heat is retained in the slot to balance the reduction in heat input caused by the reduction in the slot voltage, so that the thermal balance of normal production can be maintained, the slot temperature and related slot conditions are basically stable, and the situation that when the slot voltage of the existing slot is reduced, the heat input is reduced, and the heat dissipation cannot be reduced synchronously, and normal production cannot be maintained, and the slot voltage can only be returned to a higher level, such as when the furnace wall thickness is thin and the slot voltage reduction is small, the thickness of the aerogel material is not adjusted when the furnace wall thickness is thickened without affecting production and operation. With the blessing of being able to retain more heat in the slot, aluminum electrolysis production can be truly implemented and realized by significantly reducing the slot voltage on the existing basis (such as 4V or 3.8V). As described in

[0025] , the reduction of the electrolyte pressure drop, the reduction of the pressure drop of a single anode conductor, and the reduction of the electrolyte pressure drop that can be reduced by reducing the fluctuation of aluminum liquid can all be implemented, which allows the cell voltage of the new continuous self-baking anode electrolytic cell to be relatively stable at around 3.6 V. If the materials and technologies such as fully graphitized cathode are applied to reduce the pressure drop of the cathode, anode, electrolyte, etc., the cell operating voltage can continue to be greatly reduced, and the potential is very large.

[0026] The present invention has been described in detail above in conjunction with the embodiments of the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, other equivalent improvements can be made, all of which can achieve the purpose of the present invention and should be regarded as the protection scope of the present invention.

Claims

1. A novel continuous self-baking anode aluminum electrolysis device, comprising: Aluminum electrolytic cell body, anode structure, anode frame, support beam, asphalt fume purification device, heat insulation cover plate, gas collection feed box, characterized in that the support beam is installed and fixed on the slot edge plate of the electrolytic cell shell, and its main function is to place and fix the anode box, asphalt purification device, heat insulation cover plate, gas collection feed box, etc. The anode frame is placed and fixed on the support beam, and its main function is to shape the anode and hold the paste. The anode structure is suspended on the anode busbar, most of which is located in the anode frame, and a part extends from the lower mouth of the anode frame into the electrolyte to participate in the electrochemical reaction of aluminum electrolysis production. The asphalt fume purification device is used to treat the asphalt fume generated in the aluminum electrolysis production. The main function of the heat insulation cover plate is to completely seal the upper part of the electrolytic cell, greatly reduce the heat dissipation loss of the upper part of the cell and the leakage of smoke and dust, and eliminate or reduce the precipitation at the bottom of the furnace. The gas collection feed device allows aluminum oxide to enter and evenly add to the electrolyte liquid in the cell, collects the smoke generated during the electrolysis production here, performs a preliminary purification treatment, and then goes to the purification system for treatment.

2. The device according to claim 1, characterized in that The anode structure comprises an anode carbon body, a conductive unit group, and an anode branch bus bar.

3. The device according to claim 2, characterized in that The anode carbon body is a continuous self-baking anode, which consists of three parts: a solid anode, a liquid paste layer, and an anode particle layer. The total height is about 1200 mm, the solid anode height is about 900 mm, the anode width is about 1000 mm, and the length is about 1500 mm. The raw material is anode particles, which are composed of high-quality forged coke, residual anode fragments and high-quality asphalt, with asphalt accounting for about 20%. During production, it is located below the anode busbar, most of it is located in the anode box, and a part extends out of the lower opening of the anode box into the electrolyte. There are 4 conductive unit groups implanted in the anode carbon body, located on both sides of the anode busbar, with a spacing of about 320 mm between the two groups on the same side and a spacing of about 220 mm between the conductive unit groups on both sides. mm, so that the lower part of the produced anode is formed with 4 slit grooves, the spacing between two parallel slit grooves is about 320mm, the distance from the middle part of the anode bottom to the slit groove or the edge of the anode is less than 200mm, the escape distance of the anode bubble becomes shorter, the thickness of the bubble layer under the anode bottom is thinner, and maintaining a lower electrode distance will not reduce the current efficiency, which can reduce the electrolyte pressure drop during production by about 180mV. The bottom anode participates in the electrochemical reaction and is continuously consumed. At the same time, under the action of the Joule heat generated by the heat energy in the tank and the current passing through the inside of the anode, the anode particles and the new solid anode baked out are also continuously melted synchronously, and a certain amount of anode particles are added to the top of the anode at regular intervals. The anode structure remains stable to ensure continuous electrolytic production until the tank is stopped for overhaul and the tank is adjusted out and used again when it is restarted next time.

4. The device according to claim 2, characterized in that The anode branch busbar is made of thick aluminum plate or copper plate. The four anode branch busbars corresponding to one anode are symmetrically welded or crimped on both sides of the anode aluminum busbar. The spacing between the two branch busbars on the same side is about 320 mm. The conductive unit group is connected by multiple conductive unit buckles. The conductive unit is composed of two "7"-shaped aluminum blocks, many aluminum soft strips and a thin steel strip. The thin steel strip is on the outermost edge. The aluminum soft strip is about 400 mm long and 630 mm wide. The number of aluminum soft strips and the size of the thin steel strip are mainly determined according to the safety strength and current density of the material. Four conductive unit groups corresponding to one anode are implanted in the anode carbon body. During the upper production, they are hung on the anode branch busbars located on both sides of the anode busbar. The edge is about 7 mm away from the upper inner wall of the anode box. The spacing between the two groups on the same side is about 320 mm, and the spacing between the conductive unit groups on both sides is about 220. mm. During production, the anode raw materials shrink after being baked into solid anodes at the bottom of the anode box. The conductive unit material undergoes thermal expansion and extends out of the edge of the solid anode in the length direction of the anode. Further downward, the temperature is higher than 660°C, and the aluminum melts into molten aluminum and enters the tank. Four slit grooves are formed at the bottom of the anode. The spacing between two parallel slit grooves is about 320 mm, and the distance from the middle of the anode bottom to the slit groove or the anode edge is less than 200 mm.

5. The device according to claim 1, characterized in that The support beam is arranged and fixed on the slot edge plate of the electrolytic cell shell, and the number is N / 2+1, where N is the number of anodes in one cell. The main material is a thick stainless steel plate, and the sealing part in the slot is coated with a ceramic-based aerogel coating. An "L"-shaped groove is opened on the top of the beam, and the groove depth is about 5mm. The length of the groove is about 2mm longer than the anode box, and the width of the groove is about 1mm larger than the thickness of the anode box steel plate.

6. The device according to claim 1, characterized in that The anode frame is a rectangular frame structure assembled from multiple stainless steel plates, the number of which is the same as the number of anodes, the height is about 1400mm, the size of the frame cavity is the same as the upper carbon anode, the lower opening is placed in the "L"-shaped groove of the two support beams, the upper opening is crimped with the reinforced flat belly plate on the portal frame with fasteners, the frame in the sealing part of the heat insulation cover plate and the gas collecting feed box is coated with ceramic-based aerogel coating, an anode particle entry device is arranged on the upper outer wall of the frame side, and an anode particle distribution plate is built in, and the anode particles are added into the anode box from then on, and the anode particles fall on the top of the anode body more evenly, and a threaded pipe joint is arranged downwardly, which is connected to the asphalt smoke purification device, and in addition, a pneumatic clamping device is also arranged on the flat belly plate on the anode frame, which is composed of a cylinder and a clamping plate and is used when lifting the busbar.

7. The device according to claim 1, characterized in that The asphalt smoke purification device is composed of a main pipeline, an upper smoke pipe, a lower smoke pipe and some joints. The two main pipelines are composed of straight stainless steel pipes, bends, and flexible joints, and are symmetrically placed on the support beam. There are threaded joints on the pipelines to connect the upper smoke pipe and the lower smoke pipe. The upper smoke pipe is an assembly connected by an ordinary steel pipe and a hose, and is connected to the upper smoke exhaust hole on the outer side of each anode box. The lower smoke pipe is a high-temperature corrosion-resistant silicon nitride combined with silicon carbide tube, which is located between the two rows of anodes A and B and extends downward to about 5 cm from the surface of the high-temperature electrolyte. The asphalt smoke generated on the upper part of the anode during production passes through the pipeline of the asphalt smoke purification device and finally reaches the surface of the high-temperature electrolyte. In the small high-temperature space at about 900°C, harmful high-molecular compounds such as benzopyrene are combined into small-molecular compounds, which are burned by the oxygen introduced from the air intake pipe of the middle insulation cover plate and become harmless gases. The gases enter the gas collecting feed box for initial purification and then go to the purification system for treatment.

8. The device according to claim 1, characterized in that The thermal insulation cover plate is composed of a stainless steel plate, an aerogel composite thermal insulation material, a ceramic fireproof cloth and a silicon nitride combined with silicon carbide tube, and is divided into a middle cover plate and an edge cover plate. These thermal insulation cover plates completely seal the upper part of the electrolytic cell, eliminate or reduce the sedimentation at the bottom of the furnace, and basically no smoke and dust leakage. At the same time, since the thermal conductivity of the aerogel material is only about 0.02W / m.K and is relatively stable, it can greatly reduce the heat loss of the upper part of the cell and is easy to control. When the heat income of the electrolytic cell changes greatly, the thickness of the aerogel material in the thermal insulation cover plate can be adjusted to reduce the heat loss of the upper part of the cell, maintain the thermal balance and normal cell condition of the electrolytic cell, and provide a guarantee for the continued significant reduction of the cell voltage for electrolytic production.

9. The device according to claim 1, characterized in that The gas collecting feed box is installed on the support beam. Its main material is stainless steel coated with ceramic-based aerogel coating. It is located at the existing tank shell unloading point and consists of a box body, a feed pipe, a primary dividing plate, a secondary dividing plate, a smoking pipe, and a sealing plate. The feed pipe is connected to the alumina box unloader with a threaded connection. The smoking pipe is connected to the box body and the electrolytic cell smoke pipe with a threaded connection or a bolted connection. Its main function is to allow alumina to enter the box through a closed channel and evenly add it to the electrolyte liquid in the tank. The flue gas generated during electrolytic production is collected here for a preliminary purification and then sent to the purification system for treatment.

Citation Information

Patent Citations

  • Novel efficient environment-friendly aluminum electrolysis cell

    CN115012002A